What's the Point?: Lessons Learned from 100 Years of Artifact Hunting in Eastern Colorado. Issue 1 (February 2022) - LaBelle, Jason M.; Toft, Mike; Matsuda, Marie
ABSTRACT: Our professional understanding of the archaeological record is informed through academic research interest, the nature (tensions of time/money/location) of cultural resource management, and the ability of archaeologists to fully access diverse forms of data potentially available to them. Knowledge of eastern Colorado is poorly known, given that 40% of the state is publicly owned (federal and state) and most professional work occurs on land administered by federal agencies in western Colorado. Given this research disparity, we argue that professional archaeologists in eastern Colorado would certainly benefit from expanding their research networks to include the efforts of avocational archaeologists. Our article describes how artifact collectors have searched eastern Colorado for the past 100 years; although their methods differ from professional approaches, their cumulative efforts provide a nuanced read of the archaeological record. Differences relate to increased time spent on sites, access to a variety of landforms, and repeated visits over the long term. We present a case study on playa lake archaeology to emphasize these concepts and provide suggestions as to how archaeologists can create better partnerships to unlock potentially novel perspectives of the archaeological record.